RESEPSI AL-QUR’AN DI MEDIA SOSIAL: STUDI KASUS FILM ANIMASI NUSSA EPISODE “HIII SEREM!!!” - A'yun, Qurrata (Living Islam: Journal of Islamic Discourses, 2020)
This article examines the Qur'anic reception on social media, especially in one episode of the Nussa animated film "Hiii Serem !!!" which aired on Youtube and was watched more than 11.7 million times. This study uses the theory of al-Qur'an reception which was initiated by Ahmad Rafiq. The results show that the animated film Nussa is one of the edutainment shows for children who also perceive the Qur'an and the hadith in it. The reception in the episode "Hiii Serem !!!" is form in the exegesis reception, which was QS. Ali ‘Imran: 185 and in the functional receptions from informative aspect, that is, in order not to be afraid of people who die due to certain death for every human being. The transmission process at the reception above is also known through two agents, namely through the character Umma and the text of the conclusion of the wisdom of the story at the end of the screen. While the transformation that occurs in it can be classified into two forms, namely summation and expansion. Summarizing because not all messages of verse 185 are delivered, expansion because there are several other points in the explanation of the verse by Umma that are not found in the previous commentaries. Factors that influence these forms of reception, transmission and transformation are the form of media to deliver messages that are also different from those that already exist, namely in the form of animation/visuals that are disseminated through social media.